2012
DOI: 10.1186/1758-2946-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Avogadro: an advanced semantic chemical editor, visualization, and analysis platform

Abstract: BackgroundThe Avogadro project has developed an advanced molecule editor and visualizer designed for cross-platform use in computational chemistry, molecular modeling, bioinformatics, materials science, and related areas. It offers flexible, high quality rendering, and a powerful plugin architecture. Typical uses include building molecular structures, formatting input files, and analyzing output of a wide variety of computational chemistry packages. By using the CML file format as its native document type, Avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
5,012
1
68

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 7,675 publications
(5,105 citation statements)
references
References 40 publications
24
5,012
1
68
Order By: Relevance
“…All organic molecules used in this study were created using the Avogadro molecular editing suite. 27 In this study it has been assumed that the charge of the clay basal surface remains pH independent. Whilst it has recently been shown that the surface charge of kaolinite is pH dependent, it can be difficult to decouple how much of this effect is due to basal surfaces or clay edge sites.…”
Section: Model Setupmentioning
confidence: 99%
“…All organic molecules used in this study were created using the Avogadro molecular editing suite. 27 In this study it has been assumed that the charge of the clay basal surface remains pH independent. Whilst it has recently been shown that the surface charge of kaolinite is pH dependent, it can be difficult to decouple how much of this effect is due to basal surfaces or clay edge sites.…”
Section: Model Setupmentioning
confidence: 99%
“…24,25 All organic molecules used in this study were created using the Avogadro molecular editing suite. 26 Periodically replicated supercells contained one layer of montmorillonite composed of 84 unit cells (12 x 7 x 1), dimensions of approximately 6 x 6 x 6 nm, and a d -spacing of approximately 5 nm. Montmorillonite structures initially occupied the region 0 < z < 0.7 nm in all models, and the clay position varied little over all timescales modelled.…”
Section: Model Constructionmentioning
confidence: 99%
“…25 The initial distance between the feed piston and the upstream membrane was set to 5 nm in order to remove size effects in the feed. The distance between the permeate piston and the downstream membrane was initially set to 2 nm, and is expected to increase over the course of the simulation as feed water molecules move to the permeate side.…”
mentioning
confidence: 99%